Cerulenin inhibits unsaturated fatty acids synthesis in Bacillus subtilis by modifying the input signal of DesK thermosensor - Porrini, Lucía (2014)
Bacillus subtilis responds to a sudden decrease in temperature by transiently inducing the expression of the des gene encoding for a lipid desaturase, D5-Des, which introduces a double bond into the acyl chain of preexisting membrane phospholipids. This D5-Des-mediated membrane remodeling is controlled by the cold-sensor DesK. After cooling, DesK activates the response regulator DesR, which induces transcription of des. We show that inhibition of fatty acid synthesis by the addition of cerulenin, a potent and specific inhibitor of the type II fatty acid synthase, results in increased levels of short-chain fatty acids (FA) in membrane phospholipids that lead to inhibition of the transmembraneinput thermal control of DesK. Furthermore, reduction of phospholipid synthesis by conditional inactivation of the PlsC acyltransferase causes significantly elevated incorporation of long-chain FA and constitutive upregulation of the des gene. Thus, we provide in vivo evidence that the thickness of the hydrophobic core of the lipid bilayer serves as one of the stimulus sensed by the membrane spanning region of DesK.